Investigasi Bukti Digital Aplikasi We Chat Menggunakan Framework Integrated Digital Forensics Proses Model (IDFPM) Berbasis Sni 27037:2014 - Soni Soni; Eka Ramadhan; Desti Mualfah (INTEK : Jurnal Informatika dan Teknologi Informasi, 2021)
Social media is an alternative means of communication on smartphones, as many as 28% of the WeChat instant messenger application is used as a social interaction for the delivery of messages by senders and recipients, Cyberbullying on the WeChat application results in intimidation by users, so to deal with the crime of Cyberbullying applications WeChat on Smartphones requires a Mobile Forensic technique to identify digital evidence of verbal conversations on the WeChat ap-plication using the Framework In- tegrated Digital Forensics Process Model (IDFPM) method based on SNI 27037: 2014 which is carried out on Smartphones. WeChat application which was previously encrypted and hashing values of md5 and sha1 are authentic, as well as metadata or timestamp in the WeChat application conversation mes- sages using the Mobileedit Forensic Express Tools, and successfully implemented Frame Work Inte- grated Digital Forensic Process Model (IDFPM) based on SNI 27037: 2014 on the forensic investiga- tion process using Android Smartphone media. Keywords: Cyberbullying, WeChat, Mobile Forensics, Framework, SNI 27037: 2014